An Physiological Enzymatic Study for Atherosclerosis Patients in the City of Fallujah - Hadeel Abdelelah Abdel Razaaq (Institute of Medico-legal Publications Pvt Ltd, 2021)
Atherosclerosis is a syndrome that affects arterial blood vessels. Arteriosclerosis thickens the walls ofblood vessels as a result of accumulation of macrophages and white blood cells, and fat accumulation ismore pronounced over time. Blood pressure, smoking, obesity, lifestyle, sugar and age are risk factors.Atherosclerosis. The symptoms and signs of atherosclerosis differ depending on the arteries affected byatherosclerosis.This study was conducted in the Pharma lab in the city of Fallujah and samples were collected from theFallujah General Hospital. 50 samples were collected, 30 of which were patients with atherosclerosis and theremaining 20 samples were for healthy people. The samples included both males and females between theages of 30 to 78 years. A questionnaire was used to collect some information from patients and correctionsthat included (gender, age, blood pressure, smoking, Weight and blood sugar) and some tests were performed(Cholesterol , TG, HDL, LDL, VLDL, GOT, GPT, ALP, Albumin). The results showed a significantincrease in concentrations of Chol, TG, LDL, VLDL, GOT, GPT, ALP) in patients with atherosclerosisand a significant decrease in concentrations of both HDL and ALB in patients with atherosclerosis at theprobability level (P ? 0.05). The results also showed that males are more susceptible to arteriosclerosis thanFemales, and also showed that the greater the age, the greater the risk factors for atherosclerosis. The morerisk factors for atherosclerosis increase with increasing body mass. As for smoking, the results indicated thatit has an effect on atherosclerosis, as people who smoke have increased risk factors for atherosclerosis, anddisease risk factors increase with increased blood pressure and sugar.